(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
In the study of Romanian national identity, an important face of its self construction is the aspect of multi-varieties of what do we know about Romanian national identity. The Romanian history discourses avoid to approach this sensitive question, because of a big nationalistic dose that there is in knowing and telling Romanian history, on the Romania's past. The main goal of this endeavor aim to clarify how a variety of nationalistic movement decide to claim itself as a distinct national identity, to deliver from the authority of matrix-nation and to increase in order to became a separate nation. The new status of one of this secessionist national movement could be that of micronation. lt recognizes the brotherhood between micronation and matrix-nation, but it do not accept the supremacy of the least. The text will follow the road of rising national consciousness toward national identity as a group identity and the development of micronational identity. To be more specific, I used my scheme on Vlach or Aromanian identity, a population from Balkans, that suffered greater national influences from the Romanian national state.